Reworking of ancient tectonic amalgamation belt beneath the central north of North China Craton revealed by dense seismic observations - Zhou, Qiming; Shen, Xuzhang; Huang, He; Cheng, Siyuan; Zhang, Jian (Frontiers in Earth Science, 2022)
The North China Craton (NCC) is one of the oldest cratons in the world, and its internal tectonic belt is often used to investigate the Earth’s tectonic evolution events. During the late Mesozoic and Cenozoic, the western Pacific subduction zone caused the restructuring of NCC by damaging the craton beneath eastern NCC(ENCC), resulting in the distinct lateral differences between western(WNCC) and eastern NCC, which ultimately formed the current NCC. Furthermore, the subsequent tectonic events activated the ancient tectonic weak zones, and their traces are imprinted in the deep earth. Here, we investigated the crust structures with a high dense seismic array beneath the splice position of the eastern margin of the Khondalite belt and the northern part of the central orogenic belt in the NCC. The array included 140 short-period seismographs spaced at 2-3 km intervals, which recorded teleseismic 3-component waveforms over a one month period. P-wave receiver functions calculated from 25 teleseismic events provided an image of crustal structure. The weak Moho and Moho offset under the study area are visible in the migration image of receiver functions. The geological investigations and the rock outcrops were combined to establish the strong coupling relationship between the present surface fault-depression system and the deep structures. The deep material circulation, which governs the surface extension of the basin-range structure, is controlled by the deep material circulation is ultimately derived from the continuous subduction of the Western Pacific. The study's findings indicate that the ancient amalgamative belt might have transformed into a weak zone easily susceptible to modification by plate tectonic movements.